Differential physio-biochemical and yield responses of Camelina sativa L. under varying irrigation water regimes in semi-arid climatic conditions - Ahmed, Zeeshan (PLoS One, 2020)
Camelina sativa L. is an oilseed crop with wide nutritional and industrial applications. Because of favorable agronomic characteristics of C. sativa in a water-limiting environment interest in its production has increased worldwide. In this study the effect of different irrigation regimes (I(0) = three irrigations, I(1) = two irrigations, I(2) = one irrigation and I(3) = one irrigation) on physio-biochemical responses and seed yield attributes of two C. sativa genotypes was explored under semi-arid conditions. Results indicated that maximum physio-biochemical activity, seed yield and oil contents appeared in genotype 7126 with three irrigations (I(0)). In contrast water deficit stress created by withholding irrigation (I(1), I(2) and I(3)) at different growth stages significantly reduced the physio-biochemical activity as well as yield responses in both C. sativa genotypes. Nonetheless the highest reduction in physio-biochemical and yield attributes were observed in genotype 8046 when irrigation was skipped at vegetative and flowering stages of crop (I(3)). In genotypic comparison, C. sativa genotype 7126 performed better than 8046 under all I(1), I(2) and I(3) irrigation treatments. Because 7126 exhibited better maintenance of tissue water content, leaf gas exchange traits and chlorophyll pigment production, resulting in better seed yield and oil production. Findings of this study suggest that to achieve maximum yield potential in camelina three irrigations are needed under semi-arid conditions, however application of two irrigations one at flowering and second at silique development stage can ensure an economic seed yield and oil contents. Furthermore, genotype 7126 should be adopted for cultivation under water limited arid and semi-arid regions due to its better adaptability.